The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1074/jbc.m805959200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of p53 Is Regulated by TPX2-Aurora A in Xenopus Oocytes

Abstract: p53 is an important tumor suppressor regulating the cell cycle at multiple stages in higher vertebrates. The p53 gene is frequently deleted or mutated in human cancers, resulting in loss of p53 activity. This leads to centrosome amplification, aneuploidy, and tumorigenesis, three phenotypes also observed after overexpression of the oncogenic kinase Aurora A. Accordingly, recent studies have focused on the relationship between these two proteins. p53 and Aurora A have been reported to interact in mammalian cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 66 publications
2
24
0
Order By: Relevance
“…TPX2 is a cell cycle protein and serves a key role in the stability of the mitotic spindle (18). As a microtubule-associated protein, TPX2 tightly adheres to the mitotic spindle in mitotic cells (28). In certain tumors, overexpression of TPX2 results in centrosome amplification and heteroploidy formation (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…TPX2 is a cell cycle protein and serves a key role in the stability of the mitotic spindle (18). As a microtubule-associated protein, TPX2 tightly adheres to the mitotic spindle in mitotic cells (28). In certain tumors, overexpression of TPX2 results in centrosome amplification and heteroploidy formation (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage response (DDR): recent data show that TPX2 is involved in DDR to ionising radiations, by modulating the levels of γ-H2AX; TPX2 localises to DNA double strand breaks and interacts with DDR factors such as MDC1 (Neumayer et al, 2012). Previous data suggested a link between TPX2 and DDR: i) TPX2 is a putative substrate of the ATM/ATR kinases, as revealed in a large-scale proteomic screening (Matsuoka et al, 2007); ii) a functional interplay has been shown between Xenopus TPX2, the Aurora-A kinase and the p53 oncosuppressor (Pascreau et al, 2009). …”
Section: Functionmentioning
confidence: 98%
“…It is a microtubule-associated protein that plays an important role for the stability of the mitotic spindle [10]. Human TPX2, as a cell cycle protein [30], can closely combine with mitotic spindle in mitotic cells. TPX2 has been documented to be highly expressed in lung squamous cell carcinoma, salivary gland carcinoma, and ovarian cancer [8,9,31], but there were few reports about TPX2 expression in esophageal squamous cell carcinoma cases.…”
Section: Discussionmentioning
confidence: 99%